Chile: The road to joy is paved with obstacles - Yajima, Giuliano Toshiro (PSL Quarterly Review, 2022)
The second round of the Presidential elections in Chile marked a swing in the local political scenario. The coalition led by Gabriel Boric secured an unprecedented victory under the premise of delivering long-awaited reforms to a financially volatile, structurally fragile and deeply unequal economic structure. This paper sheds light on these three aspects of the Chilean economy, showing that its external and internal fragility feeds back on the excessive specialization and heterogeneity of the productive sectors, which in turn influence income and wealth distribution. It is argued that, in order to carry out an effective progressive agenda, the newly elected government should avoid yielding to the “discreet charm” of the Chilean bourgeoisie and its core principles – which includes fiscal prudence, minimum government intervention and financial liberalization.